Strategic Implementation of Geological-Economic Monitoring to Ensure Safer Production and Operating Conditions for the Mineral Sector Enterprises - Tošović, Radule (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The market turbulence of the ways and conditions of business of the mineral sector enterprises, especially the connection with the mineral reserves and their market specificities, requires a special strategic approach in planning, monitoring and realization of the business. The security of mineral reserves, their commercial and national profitability, as well as the variability of quality, are quite pronounced problems of production of certain mineral products related to metallic, non-metallic and energy mineral resources. The main objective is to provide conditions for increasing the security of production of mineral resources and corresponding mineral products, given the constant changes in the market of mineral resources, and on this basis, more successful business of enterprises in the mineral sector of the country, while maintaining competitiveness. In providing up-to-date data and information, the application of the method of geological-economic evaluation of mineral reserves, with the appropriate methodological structure of factors and indicators of evaluation, is of particular importance. Its application in different weather sections and changes in the mineral market leads to the definition of practically very applicable and useful geological-economic monitoring. It solves the problem of the actuality and validity of all production data relevant to the mineral raw material concerned and the realization of the production process in the company. Geological-economic monitoring, with the use of the method of comparative analysis, becomes an important strategic, managerial and economic tool, which enables safer conditions of production of mineral raw materials and mineral products, as well as more successful business of the companies of the mineral sector.